Trends and Impacts of Thai Film Content in the Past 5 Years - Chairat, Warattawan; Khamprasert, Nattida; Kodbuasri, Chanakasame (Journal of Dhamma for Life, 2024)
The research study titled "Trends and Impacts of Thai Film Content Over the Past 5 Years" aims to analyze the trends and impacts of Thai film content over the past five years (2018-2023) using content analysis and in-depth interviews. The research collected data from Thai films released during this period, as well as interviews with moviegoers, to explore and compare the popularity and reception of these films and assess the social and cultural impacts of their content. The study utilizes the Theory of Perceived Value and Acceptance and the Communication for Social Change Theory as conceptual frameworks. The research found that audience interest and reception of Thai films varied significantly based on genre and content. Films addressing intense social issues and relevant to daily life tended to be more popular. Audiences perceived that such films effectively reflected social problems, raising awareness and prompting social change. For example, films highlighting social inequality, environmental issues, and political conflicts received positive responses. Furthermore, creative storytelling techniques and high production quality played a crucial role in attracting audiences and boosting the popularity of Thai films. The content of Thai films over the past five years has significantly impacted Thai society and culture. Thai films have served as an effective medium for communicating and reflecting current social issues. The research found that these films promote awareness and social change, particularly regarding gender equality, human rights, and environmental conservation. Many viewers felt that Thai films contribute to exposing and critiquing social problems, leading to discussions and increased awareness on various topics. The Theory of Perceived Value and Acceptance and the Communication for Social Change Theory were crucial conceptual frameworks for this research. The Theory of Perceived Value and Acceptance helped analyze how audiences perceive the value of Thai film content and their acceptance of it. Meanwhile, the Communication for Social Change Theory explained how Thai films play a role in promoting awareness and social change. The research found that audiences who perceive value in Thai film content are more likely to accept and support social change initiatives. The study concludes that Thai films over the past five years have evolved in terms of content and audience perception, clearly reflecting social changes. Thai films not only entertain but also serve as powerful tools for communication and social change. The application of the Theory of Perceived Value and Acceptance and the Communication for Social Change Theory in this research has provided a deep understanding of how Thai films impact Thai society and culture